Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Research Vessel Sikuliaq - Margo Edwards; Daniel Oliver (Oceanography, 2011)

Host migration impacts on the phylogeography of Lyme Borreliosis spirochaete species in Europe - Stephanie A. Vollmer; Antra Bormane; Ruth E. Dinnis; Frederik Seelig; Andrew D. M. Dobson; David M. Aanensen; Marianne C. James; Michael Donaghy; Sarah E. Randolph; Edward J. Feil; Klaus Kurtenbach; Gabriele Margos (Environmental Microbiology, 2011)
Summary The geographic patterns of transmission opportunities of vector‐borne zoonoses are determined by a complex interplay between the migration patterns of the host and the vector. Here we examine the impact of host migration on the spread of a tick‐borne zoonotic disease, using Lyme Borreliosis (LB) spirochaetal species in Europe. We demonstrate that the migration of the LB species is dependent on and limited by the migration of their respective hosts. We note that populations of Borrelia spp. associated with birds ( Borrelia garinii and B. valaisiana ) show limited geographic structuring between countries compared with those associated with small mammals ( Borrelia afzelii ), and we argue that this can be explained by higher rates of migration in avian hosts. We also show the presence of B. afzelii strains in England and, through the use of the multi‐locus sequence analysis scheme, reveal that the strains are highly structured. This pattern in English sites is very different from that observed at the continental sites, and we propose that these may be recent introductions.

Volcanic Morphology of the East Pacific Rise Crest 9°49′–52′: Implications for volcanic emplacement processes at fast-spreading mid-ocean ridges - Gregory J. Kurras; Daniel J. Fornari; Margo H. Edwards; Michael R. Perfit; Matthew C. Smith (Marine Geophysical Research, 2000)